Rubber waterstop for deformation joint of combined concrete terrace

By using a three-layer structure of composite rubber sheet, self-adhesive rubber sheet and elastic support strip, the problem of sealing failure of traditional rubber waterstops under long-term aging and deformation is solved, achieving excellent waterproof and dynamic sealing effect and durability, and reducing construction and maintenance costs.

CN121697272APending Publication Date: 2026-03-20HANGZHOU SHOWER RUBBER ENG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511896469.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

Traditional rubber waterstops are prone to aging, hardening, and cracking under long-term ultraviolet radiation, oxygen oxidation, and temperature and humidity cycles. They also lack resilience and durability under large deformation and misalignment deformation, leading to sealing failure. The overall structure has poor fatigue resistance, making maintenance and replacement difficult and costly.

Method used

The system employs a three-layer structure consisting of a composite rubber sheet, a self-adhesive rubber sheet, and an elastic support strip. The composite rubber sheet is composed of a modified rubber sheet and a fiberglass cloth reinforcement layer. The self-adhesive rubber sheet provides strong adhesion, and the elastic support strip is made of foamed TPU material. Functional additives are prepared through chemical reactions to improve the anti-aging properties of the modified rubber sheet, ensuring that the waterstop remains sealed under various deformation conditions.

Benefits of technology

It achieves excellent waterproof and dynamic sealing effects, improves mechanical properties and aging resistance, extends service life, reduces construction and maintenance costs, adapts to dynamic deformation, and maintains contact pressure with concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of building waterproof materials, in particular to a rubber waterstop for a deformation joint of a combined concrete floor. The rubber waterstop sequentially comprises a composite rubber plate, a self-adhesive rubber sheet and an elastic supporting strip from top to bottom. The composite rubber plate is composed of a modified rubber plate and a glass fabric reinforcing layer arranged on the top of the modified rubber plate. The modified rubber plate is prepared by the following method: putting 90-110 parts by weight of a rubber base material, 4-6 parts by weight of nano zinc oxide, 1-1.5 parts by weight of stearic acid, 2-3 parts by weight of an anti-aging agent, 8-12 parts by weight of a functional aid, 20-30 parts by weight of dioctyl phthalate, 15-30 parts by weight of carbon black, 20-40 parts by weight of kaolin and 1-2 parts by weight of an accelerant into an internal mixer for mixing; performing extrusion molding on the rubber compound by adopting an extruder or a calender, and then performing cutting treatment, thereby obtaining the product. The rubber waterstop provided by the invention not only has excellent waterproof and dynamic sealing effects, but also has excellent mechanical properties and aging resistance; meanwhile, installation is flexible and efficient, and construction and later maintenance cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building waterproof materials, in particular to a combined rubber waterstop for deformation joint of concrete ground. BACKGROUND

[0002] The concrete ground structure, especially large facilities such as underground garage, urban comprehensive pipe gallery and traffic hub, will produce deformation joints due to factors such as temperature change, humidity difference and uneven settlement. The waterproof sealing of the deformation joint is the key to ensure the quality and durability of the project. The traditional rubber waterstop often faces the following problems: first, the rubber material is prone to aging, hardening and cracking under long-term ultraviolet radiation, oxygen oxidation and temperature and humidity cycles, resulting in sealing failure; second, the waterstop body is in a long-term stretched or compressed state when the deformation is large or the deformation is out of position, and the traditional foaming support strip has insufficient resilience and durability, and is prone to permanent deformation, losing the ability to support and follow the deformation; third, the overall structure has poor fatigue resistance, and peeling or damage is prone to occur between components under repeated vehicle rolling or vibration, which is difficult and costly to repair and replace.

[0003] At present, although there are waterstops improved by using glass fiber cloth reinforcement and self-adhesive installation, the durability of the core material, environmental adaptability and stability of the support structure have not been systematically solved. For example, the interface stability between the reinforcement layer and the rubber layer, the long-term anti-aging ability of the rubber matrix, and the energy dissipation and shape recovery ability of the support strip under high-frequency dynamic load are all technical problems that restrict the service life of the product in harsh environments (such as outdoor ramps and large temperature difference areas).

[0004] Based on the above, the present application provides a combined rubber waterstop for deformation joint of concrete ground to solve the above technical problems. SUMMARY

[0005] The present application provides a combined rubber waterstop for deformation joint of concrete ground, which not only has excellent waterproof and dynamic sealing effect, but also has excellent mechanical properties and aging resistance, prolonging its service life. At the same time, it is flexible and efficient to install, reducing the construction and maintenance costs.

[0006] To achieve the above purpose, the present application provides the following technical scheme: A combined rubber waterstop for deformation joint of concrete ground, the rubber waterstop comprises, from top to bottom, a composite rubber plate, a self-adhesive rubber sheet and an elastic support strip; the composite rubber plate is composed of a modified rubber plate and a glass fiber cloth reinforcement layer arranged on the top of the modified rubber plate.

[0007] Furthermore, the modified rubber sheet is prepared by the following method: by weight, 90-110 parts of rubber base material, 4-6 parts of nano zinc oxide, 1-1.5 parts of stearic acid, 2-3 parts of anti-aging agent, 8-12 parts of functional additives, 20-30 parts of dioctyl phthalate, 15-30 parts of carbon black, 20-40 parts of kaolin and 1-2 parts of accelerator are put into a mixer and mixed. Then, the mixed rubber is extruded into shape using an extruder or calender, and then cut to obtain the final product.

[0008] Furthermore, the rubber base material is selected from any one of chloroprene rubber, butyl rubber, and EPDM rubber.

[0009] Furthermore, the anti-aging agent is selected from any one of anti-aging agent 4010NA, anti-aging agent 445, anti-aging agent RD, and anti-aging agent 264.

[0010] Furthermore, the accelerator is selected from any one of accelerator TMTD, accelerator NA-22, and accelerator CZ.

[0011] Furthermore, the self-adhesive rubber sheet is prepared by the following method: by weight, 70-90 parts of natural rubber, 35-45 parts of paraffin oil, 10-20 parts of carbon black, 40-55 parts of kaolin, 30-35 parts of pine tar and 10-20 parts of terpene resin are put into a mixer and mixed. The resulting compound is then extruded and cut using an extruder.

[0012] Furthermore, the functional additive is prepared by the following method: porous alumina is uniformly dispersed in an 85-90wt% ethanol aqueous solution at a dosage ratio of 20-50 g / L. 2,6-Di-tert-butyl-4-methylphenol (2-5% by weight of ethanol) is added, and after ultrasonic dispersion, 30-50wt% of 3-aminopropyltriethoxysilane is added to the porous alumina. The pH is adjusted to 2.8-3.5 with hydrochloric acid, and then 0.5-0.8 times the weight of the porous alumina (0.5-0.8 times) of 3,5-di-tert-butyl-4-hydroxycinnamic acid is added. The mixture is stirred and reacted at 60-80℃ for 8-12 h. The reaction product is then subjected to solid-liquid separation, washed with ethanol until neutral, and then vacuum dried to obtain the final product.

[0013] Furthermore, porous alumina is prepared by the following method: aluminum isopropoxide and deionized water are mixed at a mass ratio of 1:2-2.5 and stirred at 80-90℃ for 30-40 min. Then, liquid paraffin (15-25% by mass of aluminum isopropoxide) and nitric acid aqueous solution (35-40% by mass of 60-70 wt%) are added sequentially. The mixture is stirred at 95-100℃ for 6-10 h. After distillation for 20-30 min, the mixture is dropped into an oil-ammonia column using a dropper. After standing for 2-3 h, the mixture is poured out and washed 3-5 times with isopropanol. The alumina is then dried at room temperature for 25-30 h, and then dried at 100-110℃ for 8-10 h. After high-temperature sintering and natural cooling to room temperature, the alumina is ground and passed through a 300-400 mesh sieve. During high-temperature sintering, the temperature is increased to 550-650℃ at a rate of 2-4℃ / min and calcined for 3-5 h.

[0014] Furthermore, the elastic support strip is prepared by the following method: by weight, 80-100 parts of TPU particles with a hardness of 75A, 2-4 parts of calcium stearate, 2-6 parts of azodicarbonamide and 15-25 parts of processing aids are calendered to obtain a thermoplastic polyurethane film precursor; then the thermoplastic polyurethane film precursor is placed in a foaming equipment for stepped foaming and then cut to obtain the final product; wherein, the stepped foaming successively passes through temperature ranges of 140℃, 200℃, 220℃ and 180℃, and the total foaming time is 2 minutes.

[0015] Furthermore, the processing aid is selected from any one of ACR201, ACR301, ACR401, and ACR402.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. The rubber waterstop prepared by this invention consists of a three-layer composite structure: a composite rubber sheet, a self-adhesive rubber sheet, and an elastic support strip. The composite rubber sheet provides primary waterproofing and weather resistance; the self-adhesive rubber sheet offers strong initial adhesion to the concrete substrate, allowing for flexible and efficient on-site installation (supporting Ω / V-type connections), and enabling independent replacement of individual components, thus compensating for construction defects and significantly reducing construction and subsequent maintenance costs. The elastic support strip provides continuous upward elastic support, ensuring the waterstop adheres tightly to the concrete during shrinkage and compresses elastically during expansion, effectively adapting to dynamic deformation. The self-adhesive rubber sheet formulation contains a large amount of pine tar and terpene resin, which endow it with excellent surface wettability and pressure-sensitive adhesion. During construction, simply removing the release liner allows the waterstop to be firmly adhered to the concrete substrate on one side of the expansion joint, forming a reliable first sealing barrier and greatly reducing the risk of leakage due to improper concrete pouring. Furthermore, the elastic support strip is made of foamed TPU material, prepared through a stepped foaming process, forming a foam body with suitable elasticity and a closed-cell structure. This ensures that the waterstop actively follows changes in joint width and maintains contact pressure with the concrete under various deformation conditions, achieving dynamic sealing. In addition, the fiberglass reinforcement layer on top of the composite rubber sheet effectively improves the mechanical properties of the waterstop, preventing failure due to external force damage. Through optimized formulation and process preparation, the interfacial bonding of each layer is strong, resulting in overall durability far superior to traditional single-material waterstops.

[0017] 2. This invention uses aluminum isopropoxide, liquid paraffin, and nitric acid solution as raw materials to prepare porous alumina with a spherical structure through a chemical reaction. The porous alumina is uniformly dispersed in an ethanol-water solution, and 2,6-di-tert-butyl-4-methylphenol is added and ultrasonically dispersed to ensure uniform adhesion of 2,6-di-tert-butyl-4-methylphenol to the surface and internal pore structure of the porous alumina. Then, 3,5-di-tert-butyl-4-hydroxycinnamic acid is added, allowing it to graft onto the surface and internal pore structure of the porous alumina through the "bridging" effect of 3-aminopropyltriethoxysilane, ultimately yielding a functional additive. The prepared functional additive significantly improves the antioxidant properties through the synergistic effect of porous alumina, 2,6-di-tert-butyl-4-methylphenol, and 3,5-di-tert-butyl-4-hydroxycinnamic acid. The use of the functional additive significantly improves the anti-aging properties of modified rubber sheets, effectively extending their service life. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0019] Example 1: A composite rubber waterstop for expansion joints in concrete floors, comprising, from top to bottom: a composite rubber sheet, a self-adhesive rubber sheet, and an elastic support strip; the composite rubber sheet consists of a modified rubber sheet and a fiberglass cloth reinforcement layer on top of it.

[0020] The modified rubber sheet is prepared by the following method: by weight, 90 parts of EPDM rubber, 4 parts of nano zinc oxide, 1 part of stearic acid, 2 parts of antioxidant 4010NA, 8 parts of functional additives, 20 parts of dioctyl phthalate, 15 parts of carbon black (model N220), 20 parts of kaolin and 1 part of accelerator TMTD are put into a mixer and mixed. Then, the mixed rubber is extruded into shape using an extruder or calender, and then cut to obtain the final product.

[0021] Self-adhesive rubber sheets are prepared by the following method: by weight, 70 parts of natural rubber, 35 parts of paraffin oil, 10 parts of carbon black, 40 parts of kaolin, 30 parts of pine tar and 10 parts of terpene resin are put into a mixer and mixed. The resulting compound is then extruded and cut using an extruder.

[0022] The functional additive was prepared by the following method: porous alumina was uniformly dispersed in an 85wt% ethanol aqueous solution at a dosage ratio of 20g / L. 2,6-Di-tert-butyl-4-methylphenol (2% by mass of ethanol) was added. After ultrasonic dispersion, 30wt% of 3-aminopropyltriethoxysilane (3-aminopropyltriethoxysilane) was added to the porous alumina. The pH was adjusted to 2.8 with hydrochloric acid. 3,5-Di-tert-butyl-4-hydroxycinnamic acid (0.5 times by mass of porous alumina) was added. The mixture was stirred and reacted at 60℃ for 12h. The reaction product was then subjected to solid-liquid separation, washed with ethanol until neutral, and then vacuum dried to obtain the final product.

[0023] Porous alumina is prepared by the following method: aluminum isopropoxide and deionized water are mixed at a mass ratio of 1:2 and stirred at 80°C for 40 min. Then, liquid paraffin (15% by mass of aluminum isopropoxide) and nitric acid aqueous solution (35% by mass of 60 wt%) are added sequentially. The mixture is stirred at 95°C for 10 h. After distillation for 20 min, the mixture is dropped into an oil-ammonia column using a dropper. After standing for 2 h, the mixture is poured out and washed three times with isopropanol. The alumina is then dried at room temperature for 25 h, then dried at 100°C for 10 h. Finally, it is sintered at high temperature, naturally cooled to room temperature, ground, and passed through a 300-mesh sieve. During high-temperature sintering, the temperature is increased to 550°C at a rate of 2°C / min, and calcined for 5 h.

[0024] The elastic support strip is prepared by the following method: 80 parts by weight of TPU particles with a hardness of 75A, 2 parts of calcium stearate, 2 parts of azodicarbonamide and 15 parts of processing aid ACR201 are calendered to obtain a thermoplastic polyurethane film precursor; then the thermoplastic polyurethane film precursor is placed in a foaming equipment for stepped foaming and then cut to obtain the final product; wherein, the stepped foaming passes through temperature ranges of 140℃, 200℃, 220℃ and 180℃ in sequence, and the total foaming time is 2 minutes.

[0025] Example 2: The rubber waterstop for the expansion joint of the composite concrete floor provided in this embodiment is basically the same as that in Embodiment 1, except that the preparation methods of the modified rubber sheet, self-adhesive rubber sheet and elastic support strip are not exactly the same. The specific preparation methods of the modified rubber sheet, self-adhesive rubber sheet and elastic support strip in this embodiment are as follows: The modified rubber sheet is prepared by the following method: by weight, 100 parts of EPDM rubber, 5 parts of nano zinc oxide, 1.2 parts of stearic acid, 2.5 parts of antioxidant 445, 10 parts of functional additives, 25 parts of dioctyl phthalate, 20 parts of carbon black (model N220), 30 parts of kaolin and 1.5 parts of accelerator NA-22 are put into a mixer and mixed. Then, the mixed rubber is extruded and shaped using an extruder or calender, and then cut to obtain the final product.

[0026] Self-adhesive rubber sheets are prepared by the following method: 80 parts by weight of natural rubber, 40 parts by weight of paraffin oil, 15 parts by weight of carbon black, 50 parts by weight of kaolin, 30 parts by weight of pine tar and 15 parts by weight of terpene resin are put into a mixer and mixed. The resulting compound is then extruded and cut using an extruder.

[0027] The functional additive was prepared by the following method: porous alumina was uniformly dispersed in an 85wt% ethanol aqueous solution at a dosage ratio of 40g / L. 2,6-di-tert-butyl-4-methylphenol (3% by mass of ethanol) was added, and after ultrasonic dispersion, 40wt% of 3-aminopropyltriethoxysilane was added to the porous alumina. The pH was adjusted to 3.0 with hydrochloric acid, and 0.6 times the mass of the porous alumina (0.6 times the mass of the porous alumina) of 3,5-di-tert-butyl-4-hydroxycinnamic acid was added. The mixture was stirred and reacted at 70℃ for 10h. The reaction product was then subjected to solid-liquid separation, washed with ethanol until neutral, and then vacuum dried to obtain the final product.

[0028] Porous alumina is prepared by the following method: aluminum isopropoxide and deionized water are mixed at a mass ratio of 1:2 and stirred at 85°C for 35 min. Then, liquid paraffin (20% by mass of aluminum isopropoxide) and nitric acid aqueous solution (35% by mass of 65 wt%) are added sequentially. The mixture is stirred at 100°C for 8 h. After distillation for 25 min, the mixture is dropped into an oil-ammonia column using a dropper. After standing for 3 h, the mixture is poured out and washed four times with isopropanol. The alumina is then dried at room temperature for 30 h, then dried at 105°C for 10 h. Finally, it is sintered at high temperature, naturally cooled to room temperature, ground, and passed through a 350-mesh sieve. During high-temperature sintering, the temperature is increased to 600°C at a rate of 4°C / min and calcined for 4 h.

[0029] The elastic support strip is prepared by the following method: by weight, 90 parts of TPU particles with a hardness of 75A, 3 parts of calcium stearate, 5 parts of azodicarbonamide and 20 parts of processing aid ACR301 are calendered to obtain a thermoplastic polyurethane film precursor; then the thermoplastic polyurethane film precursor is placed in a foaming equipment for stepped foaming and then cut to obtain the final product; wherein, the temperature ranges for stepped foaming are 140℃, 200℃, 220℃ and 180℃, and the total foaming time is 2 minutes.

[0030] Example 3: The rubber waterstop for the expansion joint of the composite concrete floor provided in this embodiment is basically the same as that in Embodiment 1, except that the preparation methods of the modified rubber sheet, self-adhesive rubber sheet and elastic support strip are not exactly the same. The specific preparation methods of the modified rubber sheet, self-adhesive rubber sheet and elastic support strip in this embodiment are as follows: The modified rubber sheet is prepared by the following method: by weight, 110 parts of EPDM rubber, 6 parts of nano zinc oxide, 1.5 parts of stearic acid, 3 parts of antioxidant RD, 12 parts of functional additives, 30 parts of dioctyl phthalate, 30 parts of carbon black (N220), 40 parts of kaolin and 2 parts of accelerator CZ are put into a mixer and mixed. Then, the mixed rubber is extruded into shape using an extruder or calender, and then cut to obtain the final product.

[0031] Self-adhesive rubber sheets are prepared by the following method: by weight, 90 parts of natural rubber, 45 parts of paraffin oil, 20 parts of carbon black, 55 parts of kaolin, 35 parts of pine tar and 20 parts of terpene resin are put into a mixer and mixed. The resulting compound is then extruded and cut using an extruder.

[0032] The functional additive was prepared by the following method: porous alumina was uniformly dispersed in a 90wt% ethanol aqueous solution at a dosage ratio of 50g / L. 2,6-di-tert-butyl-4-methylphenol (5% by weight of ethanol) was added, and after ultrasonic dispersion, 50wt% of 3-aminopropyltriethoxysilane (50wt% by weight of porous alumina) was added. The pH was adjusted to 3.5 with hydrochloric acid, and 0.8 times the weight of porous alumina (0.8 times by weight of 3,5-di-tert-butyl-4-hydroxycinnamic acid) was added. The mixture was stirred and reacted at 80℃ for 8 hours. The reaction product was then subjected to solid-liquid separation, washed with ethanol until neutral, and then vacuum dried to obtain the final product.

[0033] Porous alumina is prepared by the following method: aluminum isopropoxide and deionized water are mixed at a mass ratio of 1:2.5 and stirred at 90°C for 30 min. Then, liquid paraffin (25% by mass of aluminum isopropoxide) and 40% (70 wt%) nitric acid aqueous solution are added sequentially. The mixture is stirred at 100°C for 6 h. After distillation for 30 min, the mixture is dropped into an oil-ammonia column using a dropper. After standing for 3 h, the mixture is poured out and washed 5 times with isopropanol. The alumina is then dried at room temperature for 30 h, then dried at 110°C for 8 h. Finally, it is sintered at high temperature, naturally cooled to room temperature, ground, and sieved through a 400-mesh sieve to obtain the final product. During high-temperature sintering, the temperature is increased to 650°C at a rate of 4°C / min, and calcined for 3 h.

[0034] The elastic support strip is prepared by the following method: by weight, 100 parts of TPU particles with a hardness of 75A, 4 parts of calcium stearate, 6 parts of azodicarbonamide and 25 parts of processing aid ACR401 are calendered to obtain a thermoplastic polyurethane film precursor; then the thermoplastic polyurethane film precursor is placed in a foaming equipment for stepped foaming and then cut to obtain the final product; wherein, the temperature ranges for stepped foaming are 140℃, 200℃, 220℃ and 180℃, and the total foaming time is 2 minutes.

[0035] Comparative Example 1: The difference between this comparative example and Example 1 is that 2,6-di-tert-butyl-4-methylphenol was not used in the preparation of the functional additive in this comparative example.

[0036] Comparative Example 2: The difference between this comparative example and Example 1 is that in this comparative example, an equal amount of porous alumina was used to replace the functional additives when preparing the modified rubber sheet.

[0037] Performance testing: The relevant properties of the rubber waterstop samples provided in Examples 1-3 and Comparative Examples 1-2 were tested as follows, and the test data are recorded in the table below: 1. Tensile strength: The tensile strength of the sample before and after hot air aging treatment was tested according to the test method specified in Q / CR562.2-2017 "Railway Tunnel Drainage and Waterproofing Materials Part 2: Waterstop". The conditions for hot air aging treatment were: 80℃, 168h. The change rate of tensile strength after aging = (tensile strength after aging - tensile strength before aging) / tensile strength before aging × 100%.

[0038] 2. Elongation at break: According to the test method specified in Q / CR562.2-2017 "Railway Tunnel Drainage and Waterproofing Materials Part 2: Waterstops", the elongation at break of the sample before and after hot air aging treatment was tested. The conditions for hot air aging treatment were: 80℃, 168h. The change rate of elongation at break after aging = (elongation at break after aging - elongation at break before aging) / elongation at break before aging × 100%.

[0039] 3. Compression set: The compression set of the sample was tested according to the test method specified in Q / CR562.2-2017 "Railway Tunnel Drainage and Waterproofing Materials Part 2: Waterstop".

[0040] 4. Alkali resistance: The sample was placed in a saturated calcium hydroxide solution and left to stand at 23°C for 168 hours. The tensile strength and elongation at break of the sample were then tested.

[0041] 5. Ozone aging: The ozone aging performance of the samples was tested according to the test method specified in Q / CR562.2-2017 "Railway Tunnel Drainage and Waterproofing Materials Part 2: Waterstop". The aging conditions were 50×10-8, humidity 20%, and 40℃×48h.

[0042]

[0043] By comparing and analyzing the relevant data in the table, it can be seen that the rubber waterstop provided by this invention not only has excellent waterproof and dynamic sealing effects, but also excellent mechanical properties and aging resistance, extending its service life. This indicates that the composite rubber waterstop for concrete floor expansion joints provided by this invention has a broader market prospect and is more suitable for widespread application.

[0044] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0045] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A rubber waterstop for expansion joints in composite concrete floors, characterized in that, The rubber waterstop comprises, from top to bottom: a composite rubber sheet, a self-adhesive rubber sheet, and an elastic support strip; the composite rubber sheet is composed of a modified rubber sheet and a fiberglass cloth reinforcement layer on top of it.

2. The rubber waterstop for composite concrete floor expansion joints according to claim 1, characterized in that, Modified rubber sheets are prepared by the following method: by weight, 90-110 parts of rubber base material, 4-6 parts of nano zinc oxide, 1-1.5 parts of stearic acid, 2-3 parts of anti-aging agent, 8-12 parts of functional additives, 20-30 parts of dioctyl phthalate, 15-30 parts of carbon black, 20-40 parts of kaolin and 1-2 parts of accelerator are put into an internal mixer and mixed. Then, the mixed rubber is extruded into shape using an extruder or calender, and then cut to obtain the final product.

3. The rubber waterstop for composite concrete floor expansion joints according to claim 2, characterized in that: The rubber base material is selected from any one of chloroprene rubber, butyl rubber, and EPDM rubber.

4. A rubber waterstop for composite concrete floor expansion joints according to claim 2, characterized in that: The anti-aging agent is selected from any one of anti-aging agent 4010NA, anti-aging agent 445, anti-aging agent RD, and anti-aging agent 264.

5. A rubber waterstop for composite concrete floor expansion joints according to claim 2, characterized in that: The accelerator is selected from any one of accelerator TMTD, accelerator NA-22, and accelerator CZ.

6. A rubber waterstop for composite concrete floor expansion joints according to claim 1, characterized in that, Self-adhesive rubber sheets are prepared by the following method: by weight, 70-90 parts of natural rubber, 35-45 parts of paraffin oil, 10-20 parts of carbon black, 40-55 parts of kaolin, 30-35 parts of pine tar and 10-20 parts of terpene resin are put into an internal mixer and mixed. The resulting compound is then extruded and cut using an extruder.

7. A rubber waterstop for composite concrete floor expansion joints according to claim 2, characterized in that, The functional additive is prepared by the following method: porous alumina is uniformly dispersed in an 85-90wt% ethanol aqueous solution at a dosage ratio of 20-50 g / L. 2,6-Di-tert-butyl-4-methylphenol (2-5% by weight of ethanol) is added and ultrasonically dispersed. 30-50wt% of 3-aminopropyltriethoxysilane is added to the porous alumina. The pH is adjusted to 2.8-3.5 with hydrochloric acid. 0.5-0.8 times the weight of the porous alumina (0.5-0.8 times) of 3,5-di-tert-butyl-4-hydroxycinnamic acid is added. The mixture is stirred and reacted at 60-80℃ for 8-12 h. The reaction product is then subjected to solid-liquid separation, washed with ethanol until neutral, and finally dried under vacuum to obtain the final product.

8. A rubber waterstop for composite concrete floor expansion joints according to claim 7, characterized in that, Porous alumina is prepared by the following method: aluminum isopropoxide and deionized water are mixed at a mass ratio of 1:2-2.5 and stirred at 80-90℃ for 30-40 min. Then, liquid paraffin (15-25% by mass of aluminum isopropoxide) and nitric acid aqueous solution (35-40% by mass of 60-70 wt%) are added sequentially. The mixture is stirred at 95-100℃ for 6-10 h. After distillation for 20-30 min, the mixture is dropped into an oil-ammonia column using a dropper. After standing for 2-3 h, the mixture is poured out and washed 3-5 times with isopropanol. The mixture is then dried at room temperature for 25-30 h, and then dried at 100-110℃ for 8-10 h. After high-temperature sintering and natural cooling to room temperature, the mixture is ground and passed through a 300-400 mesh sieve. During high-temperature sintering, the temperature is increased to 550-650℃ at a rate of 2-4℃ / min and calcined for 3-5 h.

9. A rubber waterstop for composite concrete floor expansion joints according to claim 1, characterized in that, The elastic support strip is prepared by the following method: 80-100 parts by weight of TPU particles with a hardness of 75A, 2-4 parts of calcium stearate, 2-6 parts of azodicarbonamide, and 15-25 parts of processing aids are calendered to obtain a thermoplastic polyurethane film precursor; then the thermoplastic polyurethane film precursor is placed in a foaming equipment for stepped foaming and then cut to obtain the final product; wherein the stepped foaming passes through temperature ranges of 140℃, 200℃, 220℃, and 180℃ in sequence, and the total foaming time is 2 minutes.

10. A rubber waterstop for composite concrete floor expansion joints according to claim 9, characterized in that: The processing aid is selected from any one of ACR201, ACR301, ACR401, and ACR402.